The relationship between media and crime - Elshobake, Mohammed R. M. (Intelligentia Resources, 2022)
Crime is a phenomenon that exists in all societies. At all times and places, crimes have been committed and spread in societies regardless of the level of culture, economic, scientific, and social progress for society members, and regardless of the perpetrators of crimes and their education, culture, wealth, and poverty. The media plays a large role as one of the influences of criminal behaviour. The importance of this research is to clarify the nature of the relationship between the media and the criminal phenomenon. By following the inductive and analytical approaches, this research aims to illustrate the impact of the print, audio, visual and electronic media on the criminal phenomenon. This research concluded that the media has an influential role in the increase of the crime rate, even if it is indirectly, where broadcasting a crime on social media has contributed to the increase in its commission by others in the same country or in other countries. Therefore, the researcher recommends the necessity of imposing censorship on what is published through the media, especially electronic media, and that the family must carry its responsibility in following up and monitoring its members to evaluate their behaviour and prevent them from engaging in criminal behaviour. Finally, the researcher recommends conducting future research on the relationship between the media and the criminal phenomenon, especially the role of social media in influencing criminal behaviour.